Uncovering Diagnostic Value of Mitogenome for Identification of Cryptic Species Fusarium graminearum Sensu Stricto - Wyrębek, Joanna; Molcan, Tomasz; Myszczyński, Kamil; van Diepeningen, Anne D.; Stakheev, Alexander A.; Żelechowski, Maciej; Bilska, Katarzyna; Kulik, Tomasz (Frontiers in Microbiology, 2021)
Fungal complexes are often composed of morphologically nearly indistinguishable species with high genetic similarity. However, despite their close relationship, they can exhibit distinct phenotypic differences in pathogenicity and production of mycotoxins. Many plant pathogenic and toxigenic fungi have been shown to consist of such cryptic species. Identification of cryptic species in economically important pathogens has added value in epidemiologic studies and provides opportunities for better control. Analysis of mitochondrial genomes or ‘mitogenomics’ opens up dimensions for improved diagnostics of fungi, especially when efficient recovery of DNA is problematic. In comparison to nuclear DNA, mitochondrial DNA can be amplified with improved efficacy due to its multi-copy nature. However, to date, only a few studies have demonstrated the usefulness of mtDNA for identification of cryptic species within fungal complexes. In this study, we explored the value of mitochondrial DNA for identification of one of the most important cereal pathogens Fusarium graminearum sensu stricto (F.g.). We found that homing endonucleases (HEGs) which are widely distributed in mitogenomes of fungi display small indel polymorphism, proved to be potentially species-specific. The resulting small differences in their lengths may facilitate further differentiation of F.g. from the other cryptic species belonging to Fusarium graminearum species complex. We also explored the value of SNPs analysis of the mitogenome for typing F.g. The success in identifying F.g. strains was estimated at 96%, making this tool an attractive complement to other techniques for identification of F.g. A phylogenetic tree based on the concatenated core mitochondrial genes grouped all strains of F.g. into a well-supported, species-specific clade, which confirms the value of this approach for determining its identity.